ACCESSIBILITY AND UTILIZATION OF WATER FROM IMPROVED SOURCES AMONGST THE RURAL COMMUNITIES OF NORTHERN BAUCHI STATE, NIGERIA - Sule, Ibrahim Danladi; Momale, S. B.; Badamasi, M. M. (FUDMA Journal of Sciences, 2023)
This research examines the accessibility and utilization of water from improved sources in the rural communities of Northern Bauchi State. Field survey was used to generate data for this study; the data were collected through field observation, administration of questionnaires, interviews, focus group discussions. Multi-stage sampling was adopted in this study. The result was presented in tables, chartsand the qualitative data was presented in narrative statements. The study revealed that, prior to the construction of solar boreholes about 65% of the respondents were obtaining water from unimproved sources, while 35% was from improved sources, the situation changed with construction of the solar boreholes, 84% of the respondents obtained water from the improved sources when compared with 35% before the installation of the solar borehole. The study showsthat 69% of the respondents are of the view that construction of improved sources particularly solar borehole has significantly increases access to clean water, 28% agreed that its partially increasedaccess to clean water while 3% disagreed with that, pointing out long queues and use of human power in the solar and hand pump boreholes as thechallenges. The study concluded that theinnovation introducing solar boreholes is significantly improving access to clean water, but still much need to be done by the stakeholders to ensure wider coverage. The study recommends that in areas where access to clean water is low, solar boreholes should be provided and water development committees should be set up to manage the boreholes.
Keywords: Accessibility, Boreholes, Millennium Development Goals, Open wells.